Management Models and Development of Show Caves as Tourist Destinations in Croatia - Bočić, Neven; Lukić, Aleksandar; Opačić, Vuk Tvrtko (Acta Carsologica, 2007)
Touristic valorisation of caves has long tradition in Croatia. Research has been conducted in order to: identify show caves in Croatia (13), make an overview of their basic geomorphologic characteristics and study their role as tourist destinations. Based on Nature Protection Law and current experiences, four different management models have been identified. Management models have been recognized as an important factor for touristic valorisation of show caves. These elements as well as linkages of show caves with local economy have been examined in more details in case studies. Paper concludes with overview on current tourist development of show caves in Croatia and proposes some future actions in that respect.